2020
DOI: 10.1371/journal.pone.0232703
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy and associated factors among Human immunodeficiency virus positive patients accessing treatment at Nekemte referral hospital, west Ethiopia, 2019

Abstract: Background Antiretroviral therapy has a remarkable clinical effect in reducing the progress of Acquired Immune Deficiency Syndrome. The clinical outcome of Anti-Retroviral therapy depends on strict adherence. Poor adherence reduces the effectiveness of antiretroviral therapy and increases viral replication. With changes in service delivery over time and differences in socio-demographic status from region to region, it is essential to measure adherence. Therefore, this study aimed to assess adherence to antiret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
(58 reference statements)
7
23
1
Order By: Relevance
“…7 The finding of this study showed that study respondents who disclosed their HIV serostatus to their families were adherent to their ART medication than who did not disclose their result. This is consistent with a study that was done in West Ethiopia, 7 Northwest Ethiopia, 15 Eastern Ethiopia, 18 Southern Ethiopia, 26 Western Africa, and Sub-Saharan Africa. 13 The reason behind may be due to, when there is no expose to their HIV status, the patients may distress to take their medications, and omission would occur.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…7 The finding of this study showed that study respondents who disclosed their HIV serostatus to their families were adherent to their ART medication than who did not disclose their result. This is consistent with a study that was done in West Ethiopia, 7 Northwest Ethiopia, 15 Eastern Ethiopia, 18 Southern Ethiopia, 26 Western Africa, and Sub-Saharan Africa. 13 The reason behind may be due to, when there is no expose to their HIV status, the patients may distress to take their medications, and omission would occur.…”
Section: Discussionsupporting
confidence: 92%
“…Participants who had strong social support were found more adherent to their medication than those who have poor social support. This finding is similar to a study done in West Ethiopia, 7 Southwest Ethiopia, 6,14 Eastern Ethiopia, 18,27 Southern Ethiopia, 25 Southern-central Africa, 29 South Africa, 30 and Sub-Saharan Africa. 13 This may be due to any support from family members and friends who had direct and long-term positive influences on their ART adherence.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations